Efektivitas Metode Latihan Global dalam Meningkatkan Keterampilan Bermain Sepakbola - Endie Riyoko; Rury Rizhardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effectiveness of global exercise methods in improving soccer skills in soccer lectures. The research method used is pre-experimental research with the type of the one group pretest-posttest design which aims to see an increase in Football Playing Skills in the Football Game subject after being given the form of the Global training method and seeing the quality of learning outcomes of these subjects before and after being given the Global training method. . The research subjects were 30 students who took the Football Game course, the research subjects were determined with the consideration of the class that had Football Playing Skills problems. Data collection techniques using a football playing skills test. The data obtained were analyzed using a paired sample t-test with the help of the Statistical Product and Service Solution (SPSS) version 21.0 program. The results showed that tcount (11.57)> ttable (1.70). This means that the research hypothesis can be accepted. Thus it can be concluded that the global training method is effective in increasing the ability to play football Keywords: Global Methods, Football Skills